17=-5(3x-7)+6(-8+5x)

Simple and best practice solution for 17=-5(3x-7)+6(-8+5x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17=-5(3x-7)+6(-8+5x) equation:


Simplifying
17 = -5(3x + -7) + 6(-8 + 5x)

Reorder the terms:
17 = -5(-7 + 3x) + 6(-8 + 5x)
17 = (-7 * -5 + 3x * -5) + 6(-8 + 5x)
17 = (35 + -15x) + 6(-8 + 5x)
17 = 35 + -15x + (-8 * 6 + 5x * 6)
17 = 35 + -15x + (-48 + 30x)

Reorder the terms:
17 = 35 + -48 + -15x + 30x

Combine like terms: 35 + -48 = -13
17 = -13 + -15x + 30x

Combine like terms: -15x + 30x = 15x
17 = -13 + 15x

Solving
17 = -13 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
17 + -15x = -13 + 15x + -15x

Combine like terms: 15x + -15x = 0
17 + -15x = -13 + 0
17 + -15x = -13

Add '-17' to each side of the equation.
17 + -17 + -15x = -13 + -17

Combine like terms: 17 + -17 = 0
0 + -15x = -13 + -17
-15x = -13 + -17

Combine like terms: -13 + -17 = -30
-15x = -30

Divide each side by '-15'.
x = 2

Simplifying
x = 2

See similar equations:

| -8.5h-7.5-9.5=-15.5 | | 2x+5y-9=0 | | 6x-9=3x+11 | | y-6=-2(x+2) | | (X-10)-4=12 | | 1.1y-(y-0.6)+0.3=0 | | 3x+3(x+5)=30 | | 3-5(4x+5)=78 | | 4(-3+1)=-10(x-4)-14 | | 4x^2-98+180=0 | | 4-7(1-2r)=15.5 | | -29-x=-7x+67 | | 7(x-3)=-3x+89 | | -7+3x-2x=17 | | 5y^5=20 | | 3500+1680x=175000+550x | | 8(3n-8)=8 | | 5.9-p=2 | | x-153=55+9x | | 6.3=7.0x | | -4.5(7x-6.5)=-23.5 | | 52-4x=10-10x | | 3x-2(x-3)+4(x+1)=-5 | | 2x-102-10x=42 | | -9(5-5.5k)=26.5 | | 14-8m= | | -77-10x=165+x | | 5ab*3= | | 5r-14=-44 | | 10x-1=6x+10 | | =9xy^2+6xy-5x | | 24+8y-16w= |

Equations solver categories